2014
DOI: 10.1111/evj.12318
|View full text |Cite
|
Sign up to set email alerts
|

Disposition, behavioural and physiological effects of escalating doses of intravenously administered fentanyl to young foals

Abstract: Behavioural and physiological responses to i.v. fentanyl in young foals are dose related. As with mature horses, the window of fentanyl plasma concentrations related to possible clinically desirable actions appears relatively narrow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In preclinical settings, specific strains of rats (Lai & Lui, 2000;Weinger et al, 1995), rabbits (Soares et al, 2014), and guinea pigs (Brent & Bot, 1992) developed opioid-induced muscle rigidity and were considered potential translational animal models in relevant research fields. Furthermore, this phenomenon has been reported in other animal species as well, including equids (Knych et al, 2015) and elk (Paterson et al, 2009). Here, we describe the rare case of a Terumo Corporation, Tokyo, Japan) was infused intravenously (5-8 ml kg −1 h −1 ) through the cephalic vein.…”
Section: Introductionmentioning
confidence: 67%
“…In preclinical settings, specific strains of rats (Lai & Lui, 2000;Weinger et al, 1995), rabbits (Soares et al, 2014), and guinea pigs (Brent & Bot, 1992) developed opioid-induced muscle rigidity and were considered potential translational animal models in relevant research fields. Furthermore, this phenomenon has been reported in other animal species as well, including equids (Knych et al, 2015) and elk (Paterson et al, 2009). Here, we describe the rare case of a Terumo Corporation, Tokyo, Japan) was infused intravenously (5-8 ml kg −1 h −1 ) through the cephalic vein.…”
Section: Introductionmentioning
confidence: 67%
“…Results of clinical investigations into the effectiveness of opioid analgesia varied significantly depending on the individual horse and level of pain, with horses also showing greater variability than other species (Rowland et al, 2014). Clinical studies have also seen variations resulting from age, and some research has been conducted into the effect of some genetic variations on opioid metabolism (Knych et al, 2015; Ohta et al, 2010; Sanchez et al, 2007; Wetmore et al, 2016). Currently, the most common opioid used in equine practice is butorphanol, with morphine, fentanyl and methadone also systemically administered (Robertson et al, 2014).…”
Section: Opioids In Equine Practicementioning
confidence: 99%
“…It was shown that compound ( 138 ) affected the behavior of mice in the open field test by reducing the speed and distance of movement but did not significantly influence the research activity of animals [ 79 ]. This inhibitory effect on the motor activity of animals is characteristic of opioid analgesics [ 83 , 84 ] and analgesics, which affect the cannabinoid system, such as ∆ 9 -tetrahydrocannabinol [ 85 ]. To identify a possible mode of action, researchers studied the effect of the nonselective opioid receptor antagonist naloxone [ 86 ] and the selective cannabinoid CB1 receptor antagonist rimonabant [ 87 ] on the analgesic activity of compound ( 138 ) in the acetic acid-induced writhing test.…”
Section: Effect Of Azaadamantans On the Nervous Systemmentioning
confidence: 99%